(untitled) (Orfeu, 2023)
Originaly the old Frohsinn Theater, Teatro Carlos Gomes, in Blumenau, Santa Catarina, remodeled its physical and auditory structure throughout the development of the municipality’s history. It shows itself to be a living monument of the History of Blumenau, taken as such not only because it hosts a large part of artistic performances in Blumenau, but because it is synonymous with the representation of memories, power struggles and identities built from cultural structures. This article deals with the Teatro Carlos Gomes (Blumenau) as an object, instrument and space of power, considering in its monumentality the civilizing heritage that it carries. The text is based on documents found in the José Ferreira da Silva Historical Archive and the book commemorating the 145th anniversary of the Theater to further discuss the identity representations that the Theater evokes through its repertoire. Keywords: Teatro Carlos Gomes, History of Music in Blumenau/SC, Monument, Identity, Representation.